ANALISIS TURBULENSI LINGKUNGAN PADA KONDISI TERKINI PERILAKU PERBANKAN SYARIAH DI INDONESIA - Prasetyowati, Riris Aishah (Fakultas Ekonomi dan Bisnis Universitas Ibn Kahldun Bogor, 2013)
This research study deals with the Analysis of Turbulention of environment for assesment behaviors on Islamic Banks in Indonesia. The study adopted the methodology of questionaire survey. 8 full-fledged islamic banks in Bogor in Indonesia are used in the study. The response rate is 80% . The findings are divided into three sections : Analysis of Environmental Turbulence , Analysis of strategic of Aggresiveness , Analysis of corporate response capabilities and summarized in the gap analysis strategy. In general, the Islamic banks are be on expanding and changing situations and they are considered passive and reactive if after the event. in response capabilities of Islamic banking was rated as good by keeping or maintaining custom or tradition. The other than that Islamic banking is also being resistant to change and work to find stability in a closed system. The findings could provide insights to Islamic banks in strategic posture of considered not able to cope with environtmental turbulence that need revamping . Internal improvementin anticipation of environmental turbulence can be done by appling reengineering.